2020
DOI: 10.3390/diagnostics10100743
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Severity Score Change for Septic Shock in the Emergency Room

Abstract: The vital signs or laboratory test results of sepsis patients may change before clinical deterioration. This study examined the differences in prognostic performance when systemic inflammatory response syndrome (SIRS), Sequential Organ Failure Assessment (SOFA), quick SOFA (qSOFA) scores, National Early Warning Score (NEWS), and lactate levels were repeatedly measured. Scores were obtained at arrival to triage, 1 h after fluid resuscitation, 1 h after vasopressor prescription, and before leaving the emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
1
7
0
5
Order By: Relevance
“…Early measurements were probably made before any treatment was provided, whereas later measurements were more likely after everything possible had been done, and little more could save the patient. This hypothesis is supported by the report of Hwang et al [34] who found that the AUC of NEWS for 7-day mortality of patients with sepsis was 0.680 when measured at triage, 0.777 after resuscitation with fluid and vasopressors, and 0.888 on exiting the emergency department. Others have also shown the discrimination of NEWS to be lower on arrival to hospital than when repeated later [28,35].…”
Section: General Interpretation Of the Results In The Context Of Othe...supporting
confidence: 68%
“…Early measurements were probably made before any treatment was provided, whereas later measurements were more likely after everything possible had been done, and little more could save the patient. This hypothesis is supported by the report of Hwang et al [34] who found that the AUC of NEWS for 7-day mortality of patients with sepsis was 0.680 when measured at triage, 0.777 after resuscitation with fluid and vasopressors, and 0.888 on exiting the emergency department. Others have also shown the discrimination of NEWS to be lower on arrival to hospital than when repeated later [28,35].…”
Section: General Interpretation Of the Results In The Context Of Othe...supporting
confidence: 68%
“…Following title and abstract screening, 26 articles remained, excluding 1595 articles. From this, full texts were retrieved, and 11 studies selected for inclusion 20 21 28–36. A flow chart demonstrating this process can be seen in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The type of mortality reported varied (table 1). Three studies used 30-day or 28-day mortality as their primary outcome,29 30 36 four studies used in-hospital mortality,20 31 33 35 one study used 7-day mortality32 and one other did not specify (table 2). 34 Of the final two studies, one used a composite of ICU length of stay, vasopressor use and mortality within 72 hours of presentation,28 and the other looked at a composite of adverse outcomes, specified as either a prolonged stay in ICU ≥72 hours or in-hospital mortality 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Setores aplicados NEWS 19 DE APACHE III, MEDS, MEWS, PIRO, REMS, SAPS II, SCS, SOFA, ViEWS 20 Enfermaria eCART, MEWS, NEWS, qSOFA, SIRS, SOFA 21 DE e Enfermaria MEWS, NEWS, qSOFA, SIRS 22 DE e Enfermaria HEWS, NEWS 23 DE NEWS, qSOFA, SIRS 24 DE HEWS, NEWS2 25 Enfermaria MEWS 26 DE NEWS, qSOFA 27 Pré-hospitalar, DE e Enfermaria BTF, MEWS, NEWS, qSOFA, SIRS 28 DE e Enfermaria NEWS, qSOFA, SIRS 29 DE e Ambulatório NEWS, qSOFA, SIRS 30…”
Section: Escores Utilizadosunclassified